IDENTIFYING SPEECH ACTS USED BY MUSIC FANS: STREET INTERVIEW BY TRACK STAR SHOW ON TIKTOK - Raisa Rastom; Nor Alifah Rosaidi; Nur Asiah Syafikah Mohamad Sazali; Nor Azira Mohd Radzi (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This research qualitatively investigated the application of speech acts in street interviews done on the Track Star @trackstarshow, a popular TikTok account that connects music fans with other fans in New York. The research aims to determine the most frequent speech acts and learn how these language functions are employed in this virtual, casual setting. Drawing on John Searle’s illocutionary act theory, the research examined how speakers perform various linguistic acts through informal interviews, such as requests, assertions, questions, and compliments. Besides, this study looked at the role of speech acts in building rapport, addressing the audience, and managing social interactions. The research discovered that the speakers in the interviews used assertive, expressive and directive speech acts mostly in the selected interviews. The speakers also applied declarative statements. The findings contribute to the growing body of literature on digital communication, offering new insights into the intersection of language, media, and social interaction in digital spaces.